Land Reform dalam Kebijakan Politik Hukum Pertanahan - Zumiyati S. Ibrahim (Al-Mizan (e-Journal), 2020)
The concept of agrarian renewal has been much acclaimed and one concept that until now has not been completed in its implementation and even seems abandoned is the land policy known as "land reform". Land reform includes reforms regarding land ownership and control as well as legal relations related to land tenure. Land reform used to be an ideal that became the hope of the majority of the Indonesian people, especially poor farmers or farmers who did not have cultivated land. Agrarian reform, whose essence was land reform, was once the dominant discourse in discussing the social change in the Indonesian nation from independence to the 1960s, but the land reform program in its implementation still faces some obstacles caused by the current government's political policies which are more focused on efforts to pursue economic improvement and the existence of efforts to make land only as an object of investment and speculation, the result people or farmers landless do not increase and worse off poverty.